Environmental Context and Team Structure - Anna Stevanovic (Junior Management Science (JUMS), 2021)
Drawing on contingency and information processing theory, this study examines how environmental complexity and unpredictability influence team structure, namely the vertical hierarchy and the horizontal specification. These relationships are tested empirically using worldwide data from the video game industry covering the period 1995 to 2007. Results show that both, the levels of hierarchy and specialization, increase when teams face a complex environment. Meanwhile, the extent of vertical hierarchy as well as the degree of specialization decrease when teams are exposed to an unpredictable environment. Thereby a trade-off between emphasizing efficiency or choosing a more flexible structure exists.
Keywords: 650; Team structure; external environment; contingency theory; hierarchy; specialization